Adopting Technology in the Digital Era: A Multi Group Analysis on Employee Performance and User Ability - Ai Hartini; Novie Susanti Suseno; Gugun Geusan Akbar (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
In the era of rapidly growing digitalization, the role of technology in improving organizational performance is becoming increasingly crucial. This study was conducted to investigate how technology adoption and user skills affect employee performance at Karangmulya Health Center, Garut Regency. Through quantitative methods and a multi group analysis approach, the findings show that technology adoption has a positive impact on employee performance. In contrast, individual ability to utilize technology does not always correlate with improved performance. In particular, men appear to be more adaptive in adopting technology than women. However, education level did not show significant differences in this regard. Several barriers, such as suboptimal technology infrastructure, resistance to change, and lack of training, were identified as factors inhibiting technology adoption. Based on these findings, this study recommends a holistic approach to technology adoption strategies, emphasizing the importance of training, education, and infrastructure improvement, as well as considering the analysis of different groups to gain a more in-depth understanding.